The Harmonization Between Humans and Animals Particularly the Balinese Dog Race in Bali - Sila Adi Putra, I Ketut Agus; Darmayanthi, Eka (Jayapangus Press, 2023)
The purpose of this study was to find out how Balinese people interact with the most popular pets in Bali; Dogs. Pets are not new for the Balinese, but keeping dogs has been a trend. Also, it brings up the dog breeds that can be considered pets in Bali, such as village dogs or what is commonly known as the Kintamani Bean Dog. However, as time passed, there were various breeds of dogs on the island of the gods in different parts of the country. Bali is due to the Balinese breed dog's loyal nature, which should not be underestimated. Dogs are frequently given the same surname as the owner. Besides, dogs consider humans to be members of their pack. Dogs only slightly distinguish the owner's position from the dog's partner, who is still a group and frequently do not distinguish it. The method used in this research is descriptive qualitative. The type of research used is field research with data collection methods in the form of observation, interviews and documentation. As a result, the researcher found a long-standing spiritual and spiritual relationship between dogs and humans in Bali. Balinese people have a close relationship with pets, such as dogs, which have existed since ancient times and are not limited to pets. Bali truly values all aspects of life and knows his surroundings, including his pet dog. This research is expected to raise awareness among Balinese people about the importance of maintaining harmony with pets, particularly dogs, and preserving the Balinese purebred dog. Recent cases and phenomena involving dogs, such as rabies and the illegal dog meat trade, have alarmed the public. Things like this can be easily resolved with proper vigilance and handling. The government must consider this prevention to ensure continuity in realizing dog-human harmony in Bali.